Discovery Learning Model with Ethnopedagogy Approach in Improving Students' Comprehension Ability - Muhammad Imam Subekhi; Fakhruddin Fakhruddin; Sri Sulistyorini (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
This research objective is to analyze a validity of device and effectiveness of learning discovery learning with ethno pedagogy approaches to improve learners’ understanding concepts. Kinds of this research is quantitative approach by applying quasi experimental designs. While this research population was VI grade learners of SD Dewi Sartika Cluster, Annual District, Jawa Tengah. This research results showed that there were differences in improvement in the classes that using discovery learning model by using Ethnopedagogy approach. This approach application is able to make learning process more interactive.